Lithium Superionic Conductor Li9.42Si1.02P2.1S9.96O2.04 with Li10GeP2S12-Type Structure in the Li2S–P2S5–SiO2 Pseudoternary System: Synthesis, Electrochemical Properties, and Structure–Composition Relationships - Hori, Satoshi; Suzuki, Kota; Hirayama, Masaaki; Kato, Yuki; Kanno, Ryoji (Frontiers in Energy Research, 2016)
Lithium superionic conductors with the Li10GeP2S12 (LGPS)-type structure are promising materials for use as solid electrolytes in the next-generation lithium batteries. A novel member of the LGPS family, Li9.42Si1.02P2.1S9.96O2.04 (LSiPSO), and its solid solutions were synthesized by quenching from 1273 K in the Li2S–P2S5–SiO2 pseudoternary system. The material exhibited an ionic conductivity as high as 3.2 × 10−4 S cm−1 at 298 K, as well as the high electrochemical stability to lithium metal, which was improved by the introduction of oxygen into the LGPS-type structure. An all-solid-state cell with a lithium metal anode and LSiPSO as the separator showed excellent performance with a high reversibility of 100%. Thus, oxygen doping is an effective way of improving the electrochemical stability of LGPS-type structure.